METHODOLOGY OF FORMATION OF ECONOMIC CONTENT OF THE CONCEPT “CREDIT INSTITUTION”: EVOLUTIONARY EXCURSION - Khutorna, Myroslava; Tkachenko, Nataliya (Social Economics, 2020)
It has been found that the history of credit institutions indicates the fact of their existence in the ancient economy. Historically, it has been found that the scientific understanding of the economic content and purpose of credit institutions in economic processes begins with the emergence of the capitalist socio-economic formation. At the same time, it was found that the nature of the predominantly bank loan. Even later, representatives of classical economic theory laid down the basic postulates for understanding the role of credit institutions. Consideration of the evolution of scientific thought on the interpretation of the role of credit institutions in the system of economic relations is impossible without explaining the basic concepts. The significance of credit institutions within the framework of the naturalistic theory of credit, namely as formal intermediaries in the process of redistribution of capital, which do not create but increase capital in circulation by exchanging metal money for paper, is substantiated. Scientific analysis shows that in the framework of the capital theory of credit, the main attention is paid to credit institutions in view not only of intermediation in credit relations, but also taking into account the ability to produce credit by deposit-check issue without the exclusive need to accumulate temporarily free funds as credit resources. The urgent need to interpret the modern nature of credit institutions has been identified. A retrospective analysis of the economic content, nature and peculiarities of the functioning of a credit institution proves the existing difficulty of clearly distinguishing its characteristics that significantly distinguish it from a financial institution. The relationship between the concepts of “credit institution” and “financial institution” in the regulations of different countries is presented. On this basis, it is proved that in Ukraine, at the legislative level, a financial institution absorbs a credit institution by its functional purpose. According to the results of the study, a set of generic features of the credit institution is formulated, which allow to distinguish it among other financial intermediaries, namely: 1) the right to form financial resources by attracting funds from individuals and legal entities on terms of maturity, payment and return; 2) recognition as a legal entity that carries out professional activities in the credit market to provide loans to economic agents on its own terms and at its own risk; 3) implementation of professional mediation in the field of settlements between economic agents. The author’s interpretation of the concept of “credit institution” as a legal entity that has the right to carry out monetary intermediation, namely, is authorized to accumulate free cash of individuals and legal entities, including attracting deposits (deposits), their redistribution in compliance principles of lending, as well as the provision of other financial services in the financial market, the content and list of which is determined by the license conditions.